Discovery of a small-molecule NDR1 agonist for prostate cancer therapy - Bai, Yang; Sui, Xiuyuan; Xuan, Zuodong; Du, Yifan; Fu, Meiling; Zheng, Zeyuan; Yang, Kunao; Xu, Chunlan; Liu, Yankuo; Liu, Bin; Zhong, Min; Zhang, Zhengying; et al. (Frontiers in Pharmacology, 2024)
Prostatic cancer (PCa) is a common malignant neoplasm in men worldwide. Most patients develop castration-resistant prostate cancer (CRPC) after treatment with androgen deprivation therapy (ADT), usually resulting in death. Therefore, investigating new therapeutic targets and drugs for PCa patients is urgently needed. Nuclear Dbf2-related kinase 1 (NDR1), also known as STK38, is a serine/threonine kinase in the NDR/LATS kinase family that plays a critical role in cellular processes, including immunity, inflammation, metastasis, and tumorigenesis. It was reported that NDR1 inhibited the metastasis of prostate cancer cells by suppressing epithelial-mesenchymal transition (EMT), and decreased NDR1 expression might lead to a poorer prognosis, suggesting the enormous potential of NDR1 in antitumorigenesis. In this study, we characterized a small-molecule agonist named aNDR1, which specifically bound to NDR1 and potently promoted NDR1 expression, enzymatic activity and phosphorylation. aNDR1 exhibited drug-like properties, such as favorable stability, plasma protein binding capacity, cell membrane permeability, and PCa cell-specific inhibition, while having no obvious effect on normal prostate cells. Meanwhile, aNDR1 exhibited good antitumor activity both in vitro and in vivo. aNDR1 inhibited proliferation and migration of PCa cells and promoted apoptosis of PCa cells in vitro. We further found that aNDR1 inhibited subcutaneous tumors and lung metastatic nodules in vivo, with no obvious toxicity to the body. In summary, our study presents a potential small-molecule lead compound that targets NDR1 for clinical therapy of PCa patients.